Essentials of dance movement psychotherapy international perspectives on theory, research, and practice - Payne, Helen 1951- (Routledge, Taylor & Francis Group, 2017)
Essentials of Dance Movement Psychotherapy contributes to the global interest in embodiment approaches to psychotherapy and to the field of dance movement psychotherapy specifically. It includes recent research, innovative theories and case studies of practice providing an inclusive overview of this ever growing field. As well as original UK contributions, offerings from other nations are incorporated, making it more accessible to the dance movement psychotherapy community of practice worldwide. Helen Payne brings together well-known, experienced global experts along with rising stars from the field to offer the reader a valuable insight into the theory, research and practice of dance movement psychotherapy. The contributions reflect the breadth of developing approaches, covering subjects including: combining dance movement psychotherapy with music therapy; trauma and dance movement psychotherapy; the neuroscience of dance movement psychotherapy; the use of touch in dance movement psychotherapy; dance movement psychotherapy and autism; relational dance movement psychotherapy. It will be a treasured source for anyone wishing to learn more about the psychotherapeutic use of creative movement and dance. It will be of great value to students and practitioners in the arts therapies, psychotherapy, counselling and other health and social care professions.